Better Etiquette for Effective Paging (B.E.E.P.)—Improving Daily In-hospital Communications in the Pediatric ICU. Issue 4 (July 2021) - Chandnani, Harsha K.; Fujimoto, Shana; Wilson, Michele; Fluitt, Julie; Jones, Janae; Dehom, Salem; Tinsley, Cynthia; Lopez, Merrick
Abstract : Introduction: Paging is a vital part of patient care that allows quick contact between physicians and other hospital personnel. There was no structured way to send a page to physicians at our institution. We hypothesized that by standardizing paging format, scheduling laboratory draw times, and using order clean-up sheets, through a bundle of interventions called Better Etiquette for Effective Paging, we would decrease the number of pages received on the pediatric intensive care unit (PICU) resident pager by 15%. Methods: This project was a quality improvement initiative in a 25-bed multidisciplinary PICU in a tertiary children's hospital. Baseline data collection was performed in December 2015, categorized by time of day received and type of page. Interventions were paging standards to include relevant information, scheduling laboratory draw times, and order clean-up sheets. We collected postintervention data over 3 years to monitor for sustained change. Results: The average number of pages decreased from a baseline of 4.71 pages/patient/d in 2015 to 3.70 in 2016 (21% decrease), 3.32 in 2017 (30% decrease), and 2.74 in 2018 (42% decrease). The average PRISM 3 score remained similar in all sets (2.52, 2.50, 2.10, and 2.35). The standardized mortality ratio was not adversely affected by the decrease in pages (0.58, 1.07, 1.19, and 0). Conclusion: Standardizing the format of pages and using scheduled laboratory times with order clean-up sheets has decreased the number of pages/patient/d in the PICU by 42% without adversely affecting patient care. We can continue to improve communication among the patient care team by emphasizing efficient, standardized communication using Better Etiquette for Effective Paging.